EFEK PEMBERIAN ANABOLIK ANDROGENIK STEROID INJEKSI DOSIS RENDAH DAN TINGGI TERHADAP GAMBARAN HISTOPATOLOGI HATI DAN OTOT RANGKA TIKUS WISTAR (Rattus Novergicus) - Sari, Pamela K.; Lintong, Poppy M.; Loho, Lily L. (eBiomedik, 2015)
Abstract: Androgenic-anabolic steroids (AAS) are synthetic derivatives of the male hormone endogenous testosterone that stimulates anabolic (protein synthesis) and androgenic effects (masculinization). Long-term usage of AAS can result in liver damage. However, physiological concentrations of testosterone can stimulate protein synthesis which lead to an increase in muscle size, body mass, and endurance. This study aimed to determine the histopathology of liver and skeletal muscles of wistar rats that were given low dose and high dose injection of AAS. Subjects were 21 wistar rats divided into 7 groups. Group A was given standard pellets for 56 days (negative control), terminated on days 29,43, and 57. Group B was treated with low-dose AAS injection and standard pellets for 28 days, terminated on day 29. Group C was treated with low-dose AAS injection and standard pellets for 42 days, terminated on day 43. Group D was treated with low-dose AAS injection and standard pellets for 56 days, terminated on day 57. Group E was treated with high-dose AAS injection and standard pellets for 28 days, terminated on day 29. Group F was treated with high-dose AAS injection and standard pellets for 42 days, terminated on day 43. Group G was treated with high-dose AAS injection and standard pellets for 56 days, terminated on day 57. The results showed that the histopathology of liver and muscles in group A was still normal. In group B, the architecture of liver was still normal with a few inflammatory cells around the Kiernan triangle while in muscle the ratio of myofibril diameter was 1.28:1. In group C and group D, there were widening of the hepatic artery, bile duct, and portal vein containing blood fibrin, and inflammatory cells around the Kiernan triangle. The ratio of myofibril diameter was 1.43:1 in group C and 2.14:1 in group D. In group E, F and G, there were micro-vesicular fatty cells in the peripheral part of the liver meanwhile the myofibril diameter ratio of the muscles in group E was 1.43:1, group F 2.1:1, and group G 2.28:1. Conclusion: Administration of AAS injection of low dose and high dose for less than 4 weeks could result in inflammation, dilation of the portal vein, hepatic artery and bile duct meanwhile administration of AAS for over 4 weeks could ressult in focal fatty liver (steatosis). The administration of AAS injection of low dose and high dose for 4,6 and 8 weeks reslutid in enlargement of skeletal muscle (muscle hypertrophy).Keywords: androgenic-anabolic steroids, liver, skeletal muscleAbstrak: Anabolik Androgenik Steroid (AAS) adalah derivat sintetis dari hormon sex testosteron endogen pria, yang merangsang efek anabolik (sintesis protein) dan androgenik (maskulinisasi). Penggunaan AAS jangka panjang dapat mengakibatkan terjadinya kerusakan hati namun secara fisiologi testosteron dapat menstimulasi sintesis protein sehinggaberdampak pada peningkatan ukuran otot, massa tubuh dan ketahanan tubuh. Penelitian ini bertujuan untuk mengetahui gambaran histopatologi hati dan otot rangka wistar yang diberikan AAS injeksi dosis rendah dan dosis tinggi. Subjek penelitian 21 ekor wistar yang dibagi menjadi 7 kelompok. Kelompok A diberi pelet standar selama 56 hari (kontrol negatif), terminasi pada hari ke-29, 43, dan 57. Kelompok B diberi perlakuan AAS injeksi dosis rendah dan pelet standar selama 28 hari, terminasi hari ke-29. Kelompok C diberi AAS injeksi dosis rendah dan pelet standar selama 42 hari, terminasi hari ke-43. Kelompok D diberi AAS injeksi dosis rendah dan pelet standar selama 56 hari, terminasi hari ke-57. Kelompok E diberi perlakuan AAS injeksi dosis tinggi dan diberi pelet standar selama 28 hari, terminasi hari ke-29. Kelompok F diberi perlakuan AAS injeksi dosis tinggi dan diberi pelet standar selama 42 hari, terminasi hari ke-43. Kelompok G diberi perlakuan AAS injeksi dosis tinggi dan diberi pelet standar selama 56 hari, terminasi hari ke-57. Hasil penelitian menunjukkan pada kelompok A didapatkan gambaran histopatologi hati normal sedangkan pada otot tidak terdapat perubahan. Pada kelompok B didapatkan arsitektur hati masih normal dengan sedikit sel radang disekitar segitiga Kiernan sedangkan pada otot terlihat diameter miofibril ratio 1,28:1. Pada kelompok C dan D terlihat pelebaran arteri hepatika, duktus biliaris, dan vena porta yang berisi fibrin darah, serta sel-sel radang di sekitar segitiga Kiernan. Pada kelompok C diameter miofibril ratio 1,43;1 dan pada kelompok D 2,14:1. Pada kelompok E, F dan G terdapat sel-sel perlemakan mikrovesikuler di perifer sedangkan pada otot diameter miofibril ratio kelompok E 1,43:1, kelompok F 2,1:1, dan kelompok G 2,28:1. Simpulan: Pada pemberian AAS injeksi dosis rendah dan dosis tinggi kurang dari 4 minggu terjadi peradangan hati, pelebaran vena porta, arteri hepatika dan duktus biliaris sedangkan lebih dari 4 minggu terdapat perlemakan (steatosis) fokal hati. Pemberian AAS injeksi dosis rendah dan tinggi dalam waktu 4,6 dan 8 minggu menunjukkan pembesaran otot rangka (hipertrofi otot).Kata kunci: AAS, hati, otot rangka